PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KONSEP KERJA KARYAWAN INDOMARET PANAM PEKANBARU - Maryam Maryam; Hendripides Hendripides; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstack: this study aims to determine the effect of Motivation and Work Environment on the Work Concept. The population in this research is 24 hour indomaret employee in Kecamatan Tampan Pekanbaru consisting of 10 units of indomaret amounting to 100 people, the sample in this research is 50 employees. Sampling technique using cluster sampling. Data were collected using questionnaires or questionnaires and documentation. Data were analyzed by using multiple regression analysis, t test and F test with significant level of 0.05%. Based on the research, it is found that work motivation and work experience simultaneously have a positive and significant effect on employee work concept. This is based on the result of analysis, where the calculation result shows Fcount> Ftable (10,050> 3,18). Furthermore, by t test to determine whether each independent variable has an effect on the dependent variable. The results of partial research for the variable work motivation is obtained t arithmetic = -388 with significant value 0.700 <0.05 This shows that partially states that there is influence of motivation on employee work concept. And partial test for work environment variable is calculated = 4.472 with significant value equal to 0.000. this shows that partially states that there is influence of work environment to employee work concept. The prediction ability of both variable to work concept in research equal to 28.2%. (adjusted R Square 0.282) while the remaining 71.8% influenced by other factors not included in this study.Keywords: Motivation, Environment, and Concept.